Association between the level of knowledge, awareness, and attitude on post-COVID-19 syndrome amongst medical students in four Malaysian universities - Lee, Hao Ze; Mohammad Tony, Adam Amirudin; Ismanizan, Nurul Asyikin; Mohamad Zainal, Nurul Hayati; Omar, Norsuhana; Ku Mohd Noor, Ku Mastura; Wahid, Hanan Hamimi; Mohd Nor, Nurul Huda (Universiti Putra Malaysia, 2023)
Introduction: COVID-19 is a respiratory illness that is caused by a coronavirus. Infected people will have a chance to develop post-COVID-19 syndrome. The aim of this study is to identify the association of gender, marital status, age and university on knowledge, awareness and attitude of post-COVID-19 syndrome among medical students in four universities in Malaysia. Methods: A cross-sectional study was conducted from October 2021 to July 2022 at four universities in Malaysia which are Universiti Putra Malaysia (UPM), Universiti Islam Antarabangsa Malaysia (UIAM), Universiti Sains Malaysia (USM) and Universiti Sains Islam Malaysia (USIM). A self-administered questionnaire was administered to 355 respondents consisted of four sections, assessing socio-demographic data and knowledge, awareness and attitudes of post-COVID-19 syndrome. Results: 54.4% of the respondents had high knowledge, 53.8% had high awareness, and 55.21% had a high attitude towards post-COVID-19 syndrome. In this study, there is a significant association between knowledge on post-COVID-19 syndrome and the age among respondents. Knowledge and awareness, knowledge, and attitude as well as awareness and attitude on post-COVID-19 syndrome was also found to have significant association among respondents. Conclusion: The older age of the respondents have good knowledge towards post-COVID-19 syndrome.